How does education affect urban carbon emission efficiency under the strategy of scientific and technological innovation? - Tang, Miao miao; Xu, Dong; Lan, Qiang (Frontiers in Environmental Science, 2023)
Low-carbon economy is not only an important global topic but also a serious challenge for China's economy. Based on the panel data from the Yangtze River Delta and the Guangdong-Hong Kong-Macao Greater Bay Area urban agglomeration during 2010-2019，this paper analyzes the effects of education level, technological development and their interaction in urban carbon emission efficiency with a panel Tobit model constructed from the DEA-Undesirable model and Malmquist index model.The results show that: (1) The carbon emission efficiency of the Yangtze River Delta and the Guangdong-Hong Kong-Macao Greater Bay Area urban agglomerations shows a steady growth trend, but the overall level is low and there are regional differences, among which pure technical efficiency is the main reason limiting the improvement of comprehensive efficiency; (2) Education level and technological development have a high positive correlation on the impact of urban carbon emissions, and their interaction is conducive to the improvement of carbon emission efficiency. The carbon emission efficiency has a significant advantage under the influence of control variables such as economic development level, industrial structure upgrading, opening-up degree and Internet penetration rate. (3) According to the economic dimension and population dimension, the urban samples in the Yangtze River Delta and the Guangdong-Hong Kong-Macao Greater Bay were divided into large and small cities, and the regression results showed no substantial changes, indicating that the research conclusions are scientific. According to the above conclusions, the article puts forward the corresponding countermeasures and suggestions.